2013
DOI: 10.1097/inf.0b013e31826faede
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CD64 Expression on Neutrophils as an Early Indicator of Neonatal Sepsis

Abstract: Enhanced nCD64 reported as median M/N CD64 ratio is a highly sensitive marker of culture-positive neonatal sepsis. It additionally identifies a separate group among culture-negative sick neonates and may be useful to guide antibiotic administration especially in these neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
2
26
1
Order By: Relevance
“…This is in contrast to the majority of other infection biomarker studies for which patients are usually recruited shortly after clinical presentation (9,12,13 ). Thus, diagnostic utilities derived from these studies would also reflect the clinical assessment skills of frontline neonatologists who decided whether or not to recruit the patients.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This is in contrast to the majority of other infection biomarker studies for which patients are usually recruited shortly after clinical presentation (9,12,13 ). Thus, diagnostic utilities derived from these studies would also reflect the clinical assessment skills of frontline neonatologists who decided whether or not to recruit the patients.…”
Section: Discussionmentioning
confidence: 85%
“…However, rapid upregulation of the surface antigen occurs upon exposure to bacteria or their components (3 ). Our previous studies indicated that neutrophil CD64 possessed excellent diagnostic utility for identification of early-and late-onset sepsis and NEC at the time of clinical manifestation of these conditions (4,(7)(8)(9)(10)15 ). Nonetheless, the surveillance properties of neutrophil CD64 have not been determined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 12 included studies, seven focused specifically on neonatal sepsis. 20,[21][22][23][24]27,28 Pooled estimates of the sensitivity, specificity and accuracy of CD64 expression testing are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The initial literature search identified 67 potential studies, of which 55 were excluded to leave a total of 12 studies [11][12][13][20][21][22][23][24][25][26][27][28] for detailed review. The main reasons for excluding studies were that the study: (i) was a duplicate between the PubMed and EMBASE Õ databases; (ii) was not diagnostic; (iii) included children or adults; (iv) did not allow reconstruction of the diagnostic two-by-two table.…”
Section: Resultsmentioning
confidence: 99%